1999
DOI: 10.1089/10430349950016942
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Transgenes from Adeno-Associated Virus Vectors with the Woodchuck Hepatitis Virus Posttranscriptional Regulatory Element: Implications for Gene Therapy

Abstract: The woodchuck hepatitis virus posttranscriptional regulatory element (WPRE) evolved to stimulate the expression of intronless viral messages. To determine whether this ability to enhance expression could be useful in nonviral and heterologou s viral gene delivery systems, we analyzed the ability of the WPRE to elevate the expression of a cDNA encoding the green fluorescent protein (GFP) in these contexts. We find that the WPRE can stimulate the expression of GFP when the gene is delivered by transfection or tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
158
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(161 citation statements)
references
References 34 publications
3
158
0
Order By: Relevance
“…Use of the promoter alone in the construct rAAV-LSPhFIX resulted in very low human FIX expression in C57Bl/6 mice in the absence of these cis-acting regulatory sequences. Addition of the WPRE element increased gene expression approximately 25-fold, in agreement with previous publications, [22][23] while addition of the b-globin IVS-II intron sequence enhanced this level approximately 85-fold. Interestingly, the combination of both WPRE and intron in the same vector yielded no significant increase in gene expression in comparison to the vector containing only the intron, perhaps signifying a redundancy in these two elements in their ability to Average cFIX values are given for dog G10 between days 11 and 113.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Use of the promoter alone in the construct rAAV-LSPhFIX resulted in very low human FIX expression in C57Bl/6 mice in the absence of these cis-acting regulatory sequences. Addition of the WPRE element increased gene expression approximately 25-fold, in agreement with previous publications, [22][23] while addition of the b-globin IVS-II intron sequence enhanced this level approximately 85-fold. Interestingly, the combination of both WPRE and intron in the same vector yielded no significant increase in gene expression in comparison to the vector containing only the intron, perhaps signifying a redundancy in these two elements in their ability to Average cFIX values are given for dog G10 between days 11 and 113.…”
Section: Discussionsupporting
confidence: 92%
“…In comparison, cell culture analysis of expression levels from the two vectors showed that while the LSP promoter showed a liver-specific expression pattern, expression from the MFG promoter/intron was higher even in those liver-derived cell lines. This divergence between cell culture expression and in vivo expression levels has been observed in a number of other vector systems including hydrodynamic-based gene delivery, 20 retroviral 27 and rAAV vectors, 23 and underscores the need for careful interpretation of vector design. FIX expression following i.v.…”
Section: Delivery Of Aav-fix Vectors For Hemophilia B Tc Harding Ementioning
confidence: 96%
See 1 more Smart Citation
“…The woodchuck hepatitis virus post-transcriptional regulatory element is placed downstream of the Pomc transgene to enhance its expression [28] (Fig. 1).…”
Section: Construction Of Raav Vector Plasmidsmentioning
confidence: 99%
“…Utilizing recombinant adeno-associated viral BDNF/WPRE (rAAV/BDNF/WPRE)-mediated overexpression of BDNF 26,27 near the spinal lumbar dorsal horn after partial nerve injury, we hypothesized that chronic spinal BDNF over-expression would alleviate chronic neuropathic pain. This would provide an alternate method to cell transplants that supply the antinociceptive agent.…”
Section: With a Similar Injection Of A Control Raav-gfp Vector (Greenmentioning
confidence: 99%